Low and high-intensity water-based training equally improve disability and functional performance in women with multiple sclerosis but has no effects on IL10, IL17, and S100 protein biomarkers - Roya Askari; Maryam Jafari; Seyed Alireza Hosseini Kakhki; Masoud Etemadifar; Marzie Sadat Azarnive; Paulo Gentil; Mitra Khademosharie; Parivash Shekarchizadeh (Human Movement)
Purpose Multiple sclerosis (MS) is a demyelinating neurodegenerative disease of the central nervous system that involves a wide range of symptoms including loss of physical function. This study investigated the effects of eight weeks of water exercise training with two different intensities on Interleukin 10 (IL10), Interleukin 17 (IL17), and low molecular-weight calcium-binding proteins (S100), disability, and functional performance in women with MS.